Identifikasi Faktor Penghambat dalam Pelaksaan Standar Operasional Prosedur Kepegawaian pada Dinas Pendidikan dan Kebudayaan Kabupaten Biak Numfor - Amiruddin, Amiruddin; Dadang, A Masse; Maswati, Rani (Jurnal Administrasi dan Kebijakan Publik, 2024)
This study aims to identify Inhibiting Factors in the Implementation of SOP for Personnel at the Education and Culture Office of Biak Numfor Regency. The research method used is descriptive research using a qualitative approach. Based on the results of the study, it is known that the inhibiting factors for the Standard Operating Procedure (SOP) for Personnel Administration Services at the Education and Culture Office of Biak Numfor Regency are the availability of adequate human, financial, and technological resources that can support the smooth implementation of SOPs are inadequate, Commitment to the monitoring and evaluation system has not been effective in identifying problems and making necessary improvements. Performance Measurement, is significantly less than optimal because frequent or inconsistent policy changes can cause confusion and difficulty in following the established SOPs, limited human resources, facilities and infrastructure can hinder the implementation of SOPs properly, lack of adequate training or understanding of SOPs can hinder staff's ability to follow established procedures.